2006
DOI: 10.1002/pssc.200564148
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the charge carrier concentration in highly aluminum doped SiC using Raman scattering

Abstract: PACS 72.20. Jv, 78.30.Hv In the production of highly aluminum doped SiC bulk crystals, a need arises for a fast and simple method to estimate the hole concentration in the material for process control and optimization. An approach for a characterization method using Raman spectroscopy is presented. We established a calibration curve along with an empirical function to determine the charge carrier concentration in p-type SiC from the line width of a linear optical phonon -plasmon coupled (LOPC) mode. At char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…In another series of growth runs the doping was varied; purely n-type doped (6H-SiC:N) and purely p-type doped (6H-SiC:Al or B) crystals were grown. The doping concentration for both doping types was in the low 10 18 cm -3 range. For a reliable evaluation of the influence of these parameters on dislocation evolution it is important that all other growth conditions, which might influence dislocation formation, are kept constant in all growth runs; changes occurring due to run-to-run variations, such as temperature gradient, bending of lattice planes, etc., have to be kept minimal.…”
Section: Experiments 21 Crystal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In another series of growth runs the doping was varied; purely n-type doped (6H-SiC:N) and purely p-type doped (6H-SiC:Al or B) crystals were grown. The doping concentration for both doping types was in the low 10 18 cm -3 range. For a reliable evaluation of the influence of these parameters on dislocation evolution it is important that all other growth conditions, which might influence dislocation formation, are kept constant in all growth runs; changes occurring due to run-to-run variations, such as temperature gradient, bending of lattice planes, etc., have to be kept minimal.…”
Section: Experiments 21 Crystal Growthmentioning
confidence: 99%
“…0.2 Ω cm that meet electronic device requirements [6]. In addition, the highest in-situ n-type phosphorus doping using phosphine with chemical concentrations above 10 18 cm -3 could be realized [7]. For the quantitative electrical characterization optical techniques, such as optical absorption and Raman spectroscopy, were applied in addition to or as replacement for purely electrical measurements [8][9][10][11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…In contrast, a manifest blue shift was observed when the focal plane moved from the interface of the substrate layer and the epitaxial layer to the surface of the sample (between −7.5/−6/−5.3 µm and 0 µm defocus distance). Many studies have shown the sensitivity of the LOPC mode on carrier concentration of the n-type 4H-SiC [26][27][28][29][30]. The heavily doped n-type substrates had relatively high carrier concentrations in the orders of 10 18 cm −3 , while the n-type epitaxial layers had rather low carrier concentrations of ≈1.0 × 10 16 cm −3 comparatively.…”
Section: Depth Profiling Of Net Doping Concentrationmentioning
confidence: 99%
“…or composition (monomer or comonomer, catalyst, modifi er, crosslinker, or additive concentration, etc.) In order to quickly and nondestructively measure the hole concentration in highly aluminum doped silicon carbide (SiC) bulk crystals, the width of the 965 cm − 1 band, assigned as the longitudinal optical phonon -plasmon coupled mode, was calibrated against the charge carrier concentration [267] . Ito et al developed a laboratory -based FT -Raman method to predict the viscosity of waterborne automotive paint emulsion samples as a fi rst step towards on -line monitoring to predict fi nal product performance, such as weather durability [264] .…”
Section: Product P Ropertiesmentioning
confidence: 99%